3•2-3•4
6-12=-30
-6=-30
false
Answer:
-23/2
Step-by-step explanation:
x-5=3(x+6)
x-3x=18+5
-2x=23
x=-23/2
Multiply the length by the width and your answer will be there.
X = 2
y = 1
You can get this by replacing the y in the second equation with the 3x - 5 from the first. Then solve for x. Once you have that value, you can solve for y.
Answer:
A = 504inch
Step-by-step explanation:
Formula = A = 2(wl + hl + hw)
or A = 2wl + 2lh + 2hw, where w is the width, the l is the length, and the h is the height.
2wl = 6inch × 12inch = 72inch × 2 = 144inch
2lh = 12inch × 10inch = 120inch × 2 = 240inch
2hw = 10inch × 6inch = 60inch × 2 = 120inch
Then add all
144inch + 240inch + 120inch = 504inch
A = 504inch